A discrete limit theorem for the periodic Hurwitz zeta-function - Rimkevičienė, Audronė (Lietuvos matematikos rinkinys, 2015)
In the paper, we prove a limit theorem of discrete type on the weak convergence of probability measures on the complex plane for the periodic Hurwitz zeta-function.
Keywords: Hurwitz zeta-function; limit theorem; probability measure; weak convergence